Obtenção de ômegas monoésteres do óleo de resíduos de corvina (Macrodon ancylodon) com lipase imobilizada em epicarpo de coco Ariri (Syagrus cocoides) - FRAZÃO , Fabiana Frazão (2023)
Due to the biotechnological importance attributed to enzymes immobilized on lignocellulosic supports, this work aims to obtain monoester omegas from the oil of corvina residues (Macrodon ancylodon) with lipase immobilized in epicarp of coco ariri (Syagrus cocoides). The fish residues were obtained through a partnership with the Fish Processing Unit Carimã Frutos do Mar, located in the municipality of Raposa - MA. The oil characterization analyzes were: acid value, iodine, saponification, peroxides, density at 25°C and fatty acid profile. The research was carried out in the laboratory of the Nucleus of Fuels, Catalysis and Environment (NCCA) of the Chemistry Department of the Federal University of Maranhão - UFMA. Coconut ariri epicarp was submitted to pre treatment with hydroethanolic/alkaline extraction. The process of C. rugosa lipase immobilization in the epicarp was determined, as well as the enzymatic activity, relative activity (%) and immobilization yield (%). The FTIR and SEM characterization techniques confirmed the deposition of lipase in the treated fiber. Through the experimental planning of the Rotational Central Composite Design type –(DCCR 2²), reaction variables that affect the enzymatic activity (temperature and pH) were optimized by the Response Surface Methodology - RSM. Response surface analysis and contour curves indicated an approximate pH range of 6.5 to 7.5 and a temperature range of 36°C to 40°C for maximizing enzyme activity in both free and immobilized forms. The results showed that the optimum temperature was 35°C for free enzyme and 40°C for the biocatalyst (immobilized enzyme), presenting a reduction in its enzymatic activity for higher temperatures, so that when the temperature reaches the value of 55°C its catalytic action is almost null. The highest immobilization yield was 97.92% at 40°C and pH 7.0. As for the characterization of the oil the following results were obtained: acidity index (2.47 ± 0.00 mg KOH/g), free fatty acid (1.24 ± 0.00 in oleic acid (%), iodine index (170.17 ± 5.89 gI2/100g), peroxide (3.48 ± 0.06 meqO2/kg), saponification (176.39 ± 0.00 mgKOH/g) and density (0.86564 ± 0.00 g/cm3 ). Seventeen fatty acid methyl esters were identified from the corvina waste oil. Palmitoleic acid (C16:1) and oleic acid (C18:1) are two majority unsaturated fatty acids present. The majority saturated fatty acid was palmitic acid (C16:0). The enzymatic transesterification through the action of Candida rugosa improved the enrichment in total fatty acids. For free enzyme the total of 74.98% (saturated and unsaturated of 27.54% and 47.44%, respectively). For the immobilized lipase presented a profile of 65.03% fatty acids. In this context, the main conclusions of this work were: the DCCR 2² as a factorial planning technique through Response Surface Methodology can be an efficient tool in the study of enzymatic processes, especially the lipolytic activity of Candida rugosa lipase. The physicochemical parameters of the corvina oil were in accordance with the competent national and international standards. The study showed the possibility of the production of monoester omegas by enzymatic transesterification of fish waste oils.